A Computer Model for Simulation of Multi-Scale Phenomena in the Centrifugal Casting of Metal Matrix-Composites - L. Nastac; J. J. Valencia; H. Dong (The Minerals, Metals and Materials Society, 2000)
"A comprehensive computer model was developed to understand and optimize the centrifugal casting process for manufacturing TiC/Al-bronze friction drums. Performance of these components requires proper distribution of TiC particles, which is shown by dimensional analysis to be dominated by centrifugal buoyancy effects and solidification kinetics.The model addresses the following: (1) a rheology-viscosity model of the interference between moving particles, (2) engulfment (entrapment) or pushing of particles in the mushy region by the advancing solid/liquid interface, (3) nucleation and growth of equiaxed and eutectic phases, (4) effects of particle size, particle concentration, and cooling rate on the final grain size, and (5) the impingement effect of particles on the nucleation and growth kinetics of solidifying microstructure.Parametric studies were conducted using the computer model to investigate the effects of various process and material parameters on the distribution of TiC particles. The effects of the volume fraction, size, and morphology of the particles (including clusters and agglomerates) on the particle distribution were evaluated in detail. The complex interaction between the solidifying structure and insoluble ceramic particles in centrifugally-cast metal-matrix-composites was also investigated.The model predictions of particle distribution and microstructure were validated with experimental data for centrifugally-cast A356/SiC and TiC/Al-bronze alloys.This work was conducted by the National Center for Excellence in Metalworking Technology, operated by Concurrent Technologies Corporation under contract No. N00140-92- C-BC49 to the U.S. Navy as part of the U.S. Navy Manufacturing Technology Program."